High circulating HMGB1 indicates good prognosis in patients with advanced leiomyosarcoma under chemoimmunotherapy - Lucillia Bezu; Guido Kroemer (OncoImmunology)
Few clinical studies investigated the putative link between the activation of immunogenic cell death (ICD) and the oncological outcome. Recent data, published in a Phase 1b trial, demonstrated that an ICD-associated surge in the plasma concentration of high-mobility group box 1 (HMGB1) indicates favorable prognosis in patients with advanced leiomyosarcomas treated with the combination of doxorubicin, dacarbazine and nivolumab.